2022
DOI: 10.1017/s1742170521000478
|View full text |Cite
|
Sign up to set email alerts
|

Performance of organic farming in developing countries: a case of organic tomato value chain in Lebanon

Abstract: The future of food value chains has increasingly been reliant on the wider adoption of sustainable farming practices that include organic agriculture. Organic farming in developed countries is standardized and occupies a niche in agro-food systems. However, such a standard model, when transferred to developing countries, faces difficulty in implementation. This study aims to investigate the factors affecting the expansion of organic agriculture in Lebanon, a Middle Eastern context, and analyzes the economic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Likewise, price received and overall profitability of SFSCs are judged "good" by most of the farm businesses in the study context (Figure 1). The findings are generally consistent with the empirical evidence elsewhere (Malak-Rawlikowska et al, 2019;Vittersø et al, 2019;Abebe et al, 2022).…”
Section: Am Unable To Judge 32supporting
confidence: 91%
“…Likewise, price received and overall profitability of SFSCs are judged "good" by most of the farm businesses in the study context (Figure 1). The findings are generally consistent with the empirical evidence elsewhere (Malak-Rawlikowska et al, 2019;Vittersø et al, 2019;Abebe et al, 2022).…”
Section: Am Unable To Judge 32supporting
confidence: 91%
“…As shown in Table 3, all the horticultural producers in the study are family-owned. Several studies also reported that Lebanon has a predominantly family-based agrarian structure [40][41][42]. The first challenge for Lebanese horticultural producers relates to meeting the quality requirements of corporate buyers.…”
Section: Challenges In the Horticultural Supply Chainmentioning
confidence: 99%
“…Other promising alternative systems for small producers in Lebanon include the agrotourism model and participatory guarantee systems (PGSs). Recently, Abebe et al [41] suggested the agro-tourism model to enhance the position of organic farmers in Lebanon. PGSs have become popular in many countries, including Mexico and Brazil, as reliable alternatives to conventional third-party certifications [55][56][57].…”
Section: The Need For Alternative Food Systems and Market Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the survey by Bhatta et al (2010), the willingness to pay for organic products was found to be 78% for the price of the products, which is 20-30% higher than the inorganic products, and also found that people seek certification of the products as there are many fraud cases reported. Organic tomato farming is profitable in many developing countries (Abebe et al, 2022). In contrast, the benefit-cost ratio (B: C) was higher in Kathmandu organic farms than in conventional farms (Shrestha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%